Solving System of Fractional Order Differential Equations Using Legendre Operational Matrix of Derivatives - Salisu Ibrahim; Abdulnasir Isah (Eurasian Journal of Science and Engineering, 2021)
This paper presents approximate solutions of linear system of fractional differential equations (FDEs) by extending the approach of shifted Legendre operational matrix of derivatives together with spectral method. The results obtained in solving differential systems of linear FDE shows that the proposed method is factual. Fractional differential equations (FDEs) have been a useful tool for computing and modelling of computer components in telecommunication companies, mobile companies and for industrial practitioners and also plays a vital role in science and engineering.